The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/1479972317743757
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of cognitive impairment in patients with chronic obstructive pulmonary disease

Abstract: The aim of this study was to evaluate the clinical effects of cognitive impairment in patients with chronic obstructive pulmonary disease (COPD). A total of 91 patients with stable moderate to very severe COPD were included in this study. Cognitive functions of the patients were evaluated using the mini-mental state examination (MMSE) tool and clock-drawing test. The Brody’s Instrumental Activities of Daily Living (IADL) Questionnaire; COPD assessment test (CAT); body mass index, airflow obstruction, dyspnea, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 46 publications
1
21
1
3
Order By: Relevance
“…CI seems related to functional exercise capacity as measured by 6-minute walking distance [59,60]. Nevertheless, this was not confirmed among patients entering PR [19] or during an exacerbation [59].…”
Section: Health Outcomesmentioning
confidence: 93%
See 1 more Smart Citation
“…CI seems related to functional exercise capacity as measured by 6-minute walking distance [59,60]. Nevertheless, this was not confirmed among patients entering PR [19] or during an exacerbation [59].…”
Section: Health Outcomesmentioning
confidence: 93%
“…Several studies showed an inverse relationship between CI and HRQoL as assessed with the COPD Assessment Test [21,60], the EuroQoL-5 dimensions questionnaire [21] or St George's Respiratory Questionnaire [22]. Then again, other studies did not confirm this relationship [19,62].…”
Section: Health Outcomesmentioning
confidence: 99%
“…The prevalence of cognitive impairment (CI) among COPD patients ranges from 10 to 77% depending on diagnostic criteria and cognitive measurements [2]. It is well documented that people living with COPD exhibit greater CI compared to healthy controls [3,4], and those living with both CI and COPD are known to have difficulties in daily functioning [5][6][7], reduced adherence to treatment [8], increased risk of dementia [9] and increased risk of hospitalisation and mortality [10,11]. Some research has suggested over 40% difference in the prevalence of CI between people who experience COPD and healthy controls [4].…”
Section: Introductionmentioning
confidence: 99%
“… 2 CI in patients with COPD is mainly manifested in attention function, memory function, executive function, verbal fluency and mental-processing speed, 3–6 which affect physical performance, psychological functions and quality of life (QoL). 7 8 However, relevant research on the treatment of CI in patients with COPD is rare.…”
Section: Introductionmentioning
confidence: 99%